2014
DOI: 10.1177/1066896913501385
|View full text |Cite
|
Sign up to set email alerts
|

Endomyometriosis (“Uterus - like mass”) in an XY Male

Abstract: Male endometriosis and endomyometriosis (also termed "uterus-like mass") are 2 unusual manifestations of endometriosis. We report a case of male endomyometriosis with immunohistochemical and molecular confirmation. A 52-year-old man presented with stabbing pelvic pain. Computed tomography scan showed a mass in the right inguinal area, at the site of prior hernia repair. The lesion was tubular in shape, with a thick muscular wall and a central blood-filled lumen. Microscopically, the tissue showed layers of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 28 publications
0
21
0
1
Order By: Relevance
“…It is interesting that a man also had a ULM. [24] ULM can occur in various areas, there seems to be some elusive. The ovary is the most common site which followed by ligament of the uterus and ovary.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting that a man also had a ULM. [24] ULM can occur in various areas, there seems to be some elusive. The ovary is the most common site which followed by ligament of the uterus and ovary.…”
Section: Discussionmentioning
confidence: 99%
“…3,9,10,13,15 Various theories have also been combined to understand the unusual types of endometriosis. Although its underlying cause is uncertain, it is likely to be multifactorial and include genetic factors with possible epigenetic influences, hormonal induction and apoptosis suppression.…”
Section: Makiyanmentioning
confidence: 99%
“…8 Male endometriosis of the prostate 9 and male "uterus-like mass" are 2 unusual manifestations of endometriosis. Gonz alez RS et al 10 reported a case of male uterus-like mass (endomyometriosis) in the right inguinal area at the site of a prior hernia repair. The lesion was tubular in shape, with a thick muscular wall and a central blood-filled lumen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the presence of bundles of smooth muscle in the stroma of the lesion, as was observed in this case, is unusual. This feature makes the lesion more of a uterus-like mass or endomiometrioma [ 44 ].…”
Section: Case Presentationmentioning
confidence: 99%